Contribution of bacterial respiration to plankton respiration from 50°N to 44°S in the Atlantic Ocean. (November 2017) - García-Martín, E.E.; Aranguren-Gassis, M.; Hartmann, M.; Zubkov, M.V.; Serret, P.
Highlights: Plankton community and bacterial respiration analysed in 67 stations on the Atlantic Ocean. Higher cell-specific bacterial respiration in northern Atlantic gyre than in southern Atlantic gyre. Similar bacterial contribution to plankton community respiration within 6 Atlantic provinces. Abstract: Marine bacteria play an important role in the global cycling of carbon and therefore in climate regulation. However, the paucity of direct measurements means that our understanding of the magnitude and variability of bacterial respiration in the ocean is poor. Estimations of respiration in the 0.2–0.8 μm size-fraction (considered as bacterial respiration), total plankton community respiration, and the contribution of bacterial respiration to total plankton community respiration were made along two latitudinal transects in the Atlantic Ocean (ca. 50°N–44°S) during 2010 and 2011. Two different methodologies were used: determination of changes in dissolved O2 concentration after standard 24 h dark bottle incubations, and measurements of in vivo reduction of 2-(ρ-iodophenyl)-3-(ρ-nitrophenyl)-5phenyl tetrazolium salt (INT). There was an overall significant correlation ( r  = 0.44, p  < 0.0001, n  = 90) between the rates of community respiration estimated by both methods. Depth-integrated community respiration varied as much as threefold between regions. Maximum rates occurred in waters of the western European shelf and Patagonian shelf, and minimum rates in the North and South oligotrophic gyres. Depth-integrated bacterial respiration followed the same pattern as community respiration. There was a significantly higher cell-specific bacterial respiration in the northern subtropical gyre than in the southern subtropical gyre which suggests that bacterial carbon turnover is faster in the northern gyre. The relationships between plankton respiration and physicochemical and biological variables were different in different years. In general, INTT was correlated to both chlorophyll- a and bacterial abundance, while INT0.2–0.8 was only correlated with bacterial abundance. However, in 2010 INTT and INT0.2–0.8 were also correlated with temperature and primary production while in 2011 they were correlated with nitrate + nitrite concentration. The bacterial contribution to depth integrated community respiration was highly variable within provinces (4–77%). Results from this study suggest that the proportion of total community respiration attributable to bacteria is similar between the 6 oceanographic regions studied.